(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Data Mining is a rapidly growing area in research because of its involvement in several disciplines including Statistics, Finance, Health care, Pattern recognition, Temporal databases, Visualization, Classification and prediction, e-commerce, parallel and distributed computing. Time is an important factor for every business organization. Time includes a day, a month or a year. Mining useful pattern with time is an important issue. Traditional pattern mining techniques mainly focus on extracting different patterns. By using time factors we can found regularities and irregularities in different pattern in a particular interval. With the help of time oriented data mining techniques we can predict several important things like sufficient or insufficient quantitative of an item. This paper present an efficient approach to mine instructing pattern based on time. We proposed a new method which reduces number of database scan, execution time and different pattern for interval and subinterval Keywords: Data mining, Time, Pattern, Regularity, interval